Process optimization of service-oriented automation devices based on Petri nets - J. Marco Mendes (2010)
This paper introduces a novel method for the specification and selection of criteria-weighted operation modes for the orchestration of services in industrial automation using Petri nets. The objective is to provide to the internal decision support system of a service-oriented automation device or of another applicable computational system the capability to select the best path in a Petri net orchestration model considering different criteria to evaluate the quality of services, such as the time, energy efficiency and reliability. The transition-invariants obtained from the Petri net represent the set of possible modi operandi and these are then weighted with decision criteria. The result will be afterwards evaluated in order to select the optimal modus operandi to be executed by the device. Based on the experiments, this method permits the dynamic optimization of processes in real-time, considering available parameters from devices and other resources.